2016
DOI: 10.1245/s10434-016-5543-2
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Colorectal Cancer with Peritoneal and Liver Metastases Using Combined Liver and Cytoreductive Surgery and Hyperthermic Intraperitoneal Chemotherapy: Report from a Single-Centre Experience

Abstract: Simultaneous surgery for colorectal LM and PC is both feasible and safe, with low postoperative morbidity. Further longer-term studies would help determine its impact on patient survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 34 publications
2
33
0
Order By: Relevance
“…The full texts of the remaining 32 studies were then assessed, of which 14 were included in qualitative analysis for comparison of survival outcomes [9,10,[15][16][17][18][19][20][21][22][23][24][25][26]. Finally, 9 studies that provided sufficient data for a meta-analysis of both OS and DFS were included in a quantitative synthesis [15][16][17][18][19][20][21][22][23]. A flow diagram of the literature search procedure according to the PRISMA guidelines is shown in Figure 1.…”
Section: Results Of the Literature Search And Characteristics Of The mentioning
confidence: 99%
“…The full texts of the remaining 32 studies were then assessed, of which 14 were included in qualitative analysis for comparison of survival outcomes [9,10,[15][16][17][18][19][20][21][22][23][24][25][26]. Finally, 9 studies that provided sufficient data for a meta-analysis of both OS and DFS were included in a quantitative synthesis [15][16][17][18][19][20][21][22][23]. A flow diagram of the literature search procedure according to the PRISMA guidelines is shown in Figure 1.…”
Section: Results Of the Literature Search And Characteristics Of The mentioning
confidence: 99%
“…Patients selected for CS + HIPEC + LR presented with limited liver disease, as suggested by the median number of nodules (in general between 1 and 2), the rare occurrence of major resection and the frequent use of ablative techniques (cryotherapy, radiofrequency) [20,[29][30][31][32] [ Table 1 and Figure 1]. On the other hand, peritoneal load probably reflects the same tumor diffusion of patients selected for CS + HIPEC only, where a PCI index less than 20 is considered by the majority of referral centers as the preoperative cut-off value in selecting patients for treatment.…”
Section: Patient Selection For Cs + Hipec + Lrmentioning
confidence: 99%
“…In the same way, the mortality rates for liver resection, which was traditionally considered as one of the surgical procedures with the highest risk of death, have been lowered even more: for instance, recent series reported mortality rates less than 2%, comparable to those observed after surgery for rectal cancer [34,35] . CS + HIPEC + LR does not seem to give an additional risk of complication as the morbidity and mortality seems similar with respect to CS + HIPEC alone [20,[29][30][31][32] [ Table 2]. No study has reported a clear distinction between complication/mortality rate related to the liver resection or to the cytoreductive surgery.…”
Section: Assessment Of Morbidity and Mortalitymentioning
confidence: 99%
See 2 more Smart Citations